Pengaruh Tegangan Permukaan Terhadap Tumbukan Multiple Droplets Pada Permukaan Stainles Steel Yang Dipanaskan - Rafil Arizona (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2019)
The present study was conducted to investigate the dynamics of multiple droplets impact under various surface tensions. Here, the ethylene glycol with compositions of  0%, 5%, and 15% were injected through a nozzle into the stainless steel surface as the multiple droplets. The solid surface was heated at the temperatures of 150ºC. The dynamic of multiple droplets have been observed with frame rate of 2000 fps by a high speed camera. A technique of image processing was developed to determine the maximum droplets are spreading ratio. As the result, the surface tension contribute to the maximum spreading ratio significantly. When the droplet surface tension decreases, the maximum spreading ratio increases. The maximum spreading ratio appears when the percentage of the ethylene glycol is 15% at the temperature of 150ºC. From the visual observation, it was shown that a slower emergence of secondary droplets (droplet splashing) was carried out under low surface tension.